Synthesis of 2-ethoxycarbonylthieno[2, 3-b]quinolines in biomass-derived solvent γ-valerolactone and their biological evaluation against protein tyrosine phosphatase 1B. Issue 6 (14th January 2021) - Mu, Xu-Yang; Wang, Zhi-Jia; Feng, Bo; Xu, Lei; Gao, Li-Xin; Satheeshkumar, Rajendran; Li, Jia; Zhou, Yu-Bo; Wang, Wen-Long
Abstract : A series of 2-ethoxycarbonylthieno[2, 3- b ]quinolines were synthesized in the bio-derived "green" solvent γ-valerolactone and evaluated for their inhibitory activities against PTP1B, compound 6a displayed an IC50 value of 8.04 ± 0.71 μM with 4.34-fold preference over TCPTP. Abstract : A series of 2-ethoxycarbonylthieno[2, 3- b ]quinolines were synthesized in the bio-derived "green" solvent γ-valerolactone (GVL) and evaluated for their inhibitory activities against PTP1B, the representative compound 6a displayed an IC50 value of 8.04 ± 0.71 μM with 4.34-fold preference over TCPTP. These results provided novel lead compounds for the design of inhibitors of PTP1B as well as other PTPs.